Implementation of a Lesson Study on Pascal's Law Using Liveworksheet-Based E-Student Worksheets Media to Analyze the Learning Process in Junior High School - Andista Candra Yusro; Riris Nurhilyatuz Zulfa; Moh. Ahsanul Taqwim; Puspananda Damayanti (Berkala Ilmiah Pendidikan Fisika, 2023)
Lesson studies have long been used to increase a teacher's professionalism in designing a lesson. Lesson study consists of the plan, do, and see (reflection) stages. The lesson study research was carried out in class VIII-H on January 11, 2023, to analyze the learning process conducted by the model teacher. The results of the observer's assessment showed that learning had gone well and was interactive. The implementation of learning by the teacher is also following the lesson plan. The cognitive assessment results in grade VIII junior high school using the live worksheet-based E-LKPD media revealed that 41% of students scored higher than the standard passing score, and 59% scored lower than the passing grade standard score. Teachers must continue to provide reinforcement, particularly regarding mathematical calculations on science topics.